2015
DOI: 10.1503/cjs.010014
|View full text |Cite
|
Sign up to set email alerts
|

In search of the best reconstructive technique after pancreaticoduodenectomy: pancreaticojejunostomy versus pancreaticogastrostomy

Abstract: In search of the best reconstructive technique after pancreaticoduodenectomy: pancreaticojejunostomy versus pancreaticogastrostomyBackground: It has been suggested that pancreaticogastrostomy (PG) is a safer reconstruction than pancreaticojejunostomy (PJ), resulting in lower morbidity, including lower pancreatic leak rates and decreased postoperative mortality. We com pared PJ and PG after pancreaticoduodenectomy (PD). Methods:A randomized clinical trial was designed. It was stopped with 50% accrual. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 29 publications
2
35
1
2
Order By: Relevance
“…Finally, 122 studies were included. Of those 122 studies, 110 studies 3, [13][14][15][17][18][19][20][21][22][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127] were included in both qualitative synthesis and meta-analysis and 12 16,[128][129][130][131][132][133][134][135][136][137][138] only in the qualitative synthesis (eTable 2).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 122 studies were included. Of those 122 studies, 110 studies 3, [13][14][15][17][18][19][20][21][22][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127] were included in both qualitative synthesis and meta-analysis and 12 16,[128][129][130][131][132][133][134][135][136][137][138] only in the qualitative synthesis (eTable 2).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Classification of PT including more than 3 groups was rarely used. 3,130 The prevalence rates of soft, intermediate and hard pancreas were reported in Table 1. Of note, the terms used for "soft", "intermediate" and "hard" PT varied considerably among studies.…”
Section: Definitions and Prevalence Of Different Pt Groupsmentioning
confidence: 99%
“…All studies, except Duffas et al [ 22 ], had the rate of POPF as primary outcome. Four studies [ 21 , 24 , 26 , 29 ] did not report the duration of follow-up. In the other six studies, follow-up varied from 30 days to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Only two trials [ 11 , 22 ] reported the blinding of participants and personnel and the blinding of outcome assessment. Only in the study of Grendar et al [ 26 ], incomplete outcome data and possible selective reporting were detected. There was almost perfect agreement between the two investigators (Cohen's k statistic: 82.3% P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…They suggest that PG anastomosis reduces the rate and severity of POPF [34,37,[39][40][41][42]. However, other studies and randomized trials show no difference in the rates of POPF and overall complications [18,43].…”
Section: Discussionmentioning
confidence: 99%